Pedagogical grammar as the framework of TEFL research. Part 14. Age and foreign language acquisition: experimental data - L. Chernovaty (Викладання мов у вищих навчальних закладах освіти на сучасному етапі: Міжпредметні зв'язки, 2023)
The paper presents a comparative analysis of various groups of data (language acquisition speed, quality of language acquisition, comparative acquisition efficiency depending on the period of exposure, adult-child, and younger-children versus older-childrenʼs differences in acquisition) obtained in different experiments over a substantial time span. As it follows from the experimental studies analysis, there is conflicting data regarding the existence of a “critical age” for the foreign language acquisition and its specific limits. Much of the data can be interpreted in various ways. Differences between adults and children, older children and younger children can be explained not only by the existence of the “critical age”, but also by other reasons. The advantage of older students may be explained by their better memory, which allows them to learn a large number of clichés with which they successfully communicate, even having a very limited supply of language material. In general, basing on the available data, it is hardly possible to state that there is any age boundary in human life beyond which the foreign language acquisition is impossible or difficult to any serious degree. Experimental data, while contradictory, do not give rise to a straightforward conclusion about the advantage of any age group in any aspect of language. In short-time courses, adults progress faster but on longer stretches, children close the gap and even outpace adults. There are quite a few differences in language acquisition between adults and children, as well as older and younger children, but these differences are probably not due to the existence of a “critical age”, but to other factors discussed in the paper. It is likely that adults can learn language just as effectively as children provided the factors that impede their learning (strong instrumental and integrative motivation, absence of unfavorable affective factors, etc.) are eliminated. However, this assumption requires further research.